Bullying of adolescent in Yogyakarta: Responses and impacts - Ema Waliyanti; Farhah Kamilah (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: Phenomena of bullying for adolescents in Indonesia require a serious concern from the government, schools and parents. A high number of bullying incidents on adolescents can have negative impact physically and psychologically for actors and victims. Adolescent responses on bullying can be indicated as self-defence of a victim when being bullied.Objective: This research aimed to identify adolescent responses on bullying and its impacts for the adolescents in Yogyakarta.Methods: This study used a qualitative method of phenomenology. Data in this study were collected through observation and in-depth interviews. Participants included in this study were 14 people who consists of parents, adolescents, and teachers, and they were determined by purposive sampling. Validating of the data was conducted by using methodological triangulation, data triangulation and peer debriefing. Thematic data analysis was conducted by using the open code software 4.02.Results: This study found that the responses of adolescents to the bullying included resistance, avoidance, silence, and fear. Then impacts of the bullying could make the victims have avoidant personality disorder or shift them as actors. For actors, they would feared by his friend at school and get punishment from the school.Conclusion: Prevention of bullying of adolescents is urgently needed to overcome the impacts for the adolescents. The results of this study could be used as basic data to deal with bullying of the adolescents.